2021
DOI: 10.3390/biomedicines9091259
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Biological Destruction by Cold Atmospheric Plasma: Capability and Mechanism

Abstract: Cold atmospheric plasma (CAP) is a near-room-temperature, partially ionized gas composed of reactive neutral and charged species. CAP also generates physical factors, including ultraviolet (UV) radiation and thermal and electromagnetic (EM) effects. Studies over the past decade demonstrated that CAP could effectively induce death in a wide range of cell types, from mammalian to bacterial cells. Viruses can also be inactivated by a CAP treatment. The CAP-triggered cell-death types mainly include apoptosis, necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 173 publications
(325 reference statements)
0
26
0
Order By: Relevance
“…LTP produces oxidative stress. RONS, charged particles, ultraviolet radiation and electromagnetic fields, all of which can play a role and produce synergy in the therapy of cancer [41]. Among them, RONS is the most important element of LTP to kill tumors.…”
Section: The Oxidative Stress Toxicity Of Ltpmentioning
confidence: 99%
See 1 more Smart Citation
“…LTP produces oxidative stress. RONS, charged particles, ultraviolet radiation and electromagnetic fields, all of which can play a role and produce synergy in the therapy of cancer [41]. Among them, RONS is the most important element of LTP to kill tumors.…”
Section: The Oxidative Stress Toxicity Of Ltpmentioning
confidence: 99%
“…The uptake of tumor antigens by dendritic cells was increased. Then, DCs presented tumor antigens to anti-tumor T cells [41] (Figure 3). Lin [49]…”
Section: Ltp Induces Immunogenic Cell Deathmentioning
confidence: 99%
“…Therapies targeting TRAIL (TNF (tumor necrosis factor)-related apoptosis-inducing ligand) 8 and cyclin-dependent kinases (CDK) or cell cycle regulators 9 have been used with limited success. In recent years Cold atmospheric plasma (CAP) technology that utilizes ionized gas to selectively induce apoptosis in cancer cells has shown very encouraging results 10 13 . Preclinical In vivo studies in mouse models for various cancers, CAP treatment have demonstrated to effectively reduce tumor growth rate and induce cancer cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, low temperature plasma has been demonstrated to be effective as a therapeutic tool for the treatment of infections [ 8 , 9 ] and wound healing [ 10 , 11 , 12 ]. Since they are known to efficiently produce atomic and molecular species in both the ground electronic state (such as NO, the hydroxyl radical OH, and atomic oxygen) and vibrationally- or electronically-excited states (with internal energies ranging from 0.1 eV to beyond 10 eV), low temperature plasmas are capable of driving chemistry far from thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Since they are known to efficiently produce atomic and molecular species in both the ground electronic state (such as NO, the hydroxyl radical OH, and atomic oxygen) and vibrationally- or electronically-excited states (with internal energies ranging from 0.1 eV to beyond 10 eV), low temperature plasmas are capable of driving chemistry far from thermal equilibrium. Consequently, plasma has been applied successfully to wound healing [ 13 , 14 ], tissue regeneration [ 15 , 16 ], bacterial inactivation [ 8 , 17 ], and cancer treatment [ 18 , 19 ]. In addition, this occurs in the absence of the significant heating of tissue or organs.…”
Section: Introductionmentioning
confidence: 99%